Effectiveness of Persian-adapted Barton reading program on reading self-concept and attitude, and motivation towards reading among dyslexic student - Mihandoost, Zeinab (2011)
This research dealt with the effects of the Persian Adapted Barton program on reading self-concept, motivation toward reading, reading attitude and reading skills. The study included 64 students with dyslexia, from grades 4 and 5 in a public school in Ilam, Iran. The subjects were randomly assigned equally to two groups, namely the control and the experimental groups with each group consisting of 32 dyslexic students. The Persian Adapted Barton program was used as the research intervention for the experimental group, for a period of three months. The scales for reading attitude, reading self-concept, motivation toward reading, and reading skills were employed for the measurement of the above variables. Pretest and posttest scores on reading attitude, reading self-concept, motivation toward reading and reading skills were analyzed using repeated measures ANOVA and MANOVA. The results of the posttest indicated significant differences for reading self-concept, reading attitude, motivation toward reading and reading skills between the control and experimental groups. The results from repeated measures ANOVA illustrated statistically significant differences in reading self-concept (F=18.65, p=.001), reading attitude (F=42.79, p=.001) and motivation toward reading (F=34.22, p=.001) between the experimental and control groups. Furthermore, the results from MANOVA in reading skills (comprehension, phonics, fluency) showed statistically significant difference (F=6.31, p =.001) between the experimental and control groups. Findings showed that the Persian Adapted Barton program was effective in improving motivation toward reading, reading self-concepts, reading attitude, and reading skills of dyslexic students.